The role of serum Pro- and Anti-inflammatory cytokines as potential diagnostic markers for psoriasis - Erdal, Berna; Albayrak, Hulya; Aydin Kurc, Mine; Varol, Gamze; Emin Yanik, Mehmet; Erfan, Gamze; Gulen, Dumrul (Annals of Medical Research, 2021)
Aim: Cytokines secreted by T helper cell subgroups are considered to play chief roles in the complex pathobiology of psoriasis. Herein, we aimed to reveal the effects of anti- and pro-inflammatory cytokines on the pathobiology of psoriasis disease and the correlation of these cytokines with severity of psoriasis. Materials and Methods: Thirty-seven individuals diagnosed with psoriasis and 37 healthy control subjects were enrolled for the study. The levels of Tumor necrosis factor alpha (TNFα), Soluble CD40 ligand (sCD40L), Interferon gamma (IFNγ) and Interleukin (IL) 1β, IL4, IL6, IL10, IL17F, IL17A, IL21, IL22, IL23, IL25, IL31, IL33 were determined by the Luminex method. Results: The IL6, IFNγ, TNFα, sCD40L, IL17F, IL17A, IL23, IL25, and IL31 levels were found to be markedly advanced in individuals with psoriasis in contrast to the control group (p=0.003, p=0.02, p0.001, p=0.02, p=0.03, p=0.003, p=0.04, p=0.04, and p0.05).Conclusion: IFNγ, IL6, TNFα, sCD40L, IL17F, IL17A, IL23, IL31, IL25 and inflammatory markers were markedly advanced in patients with psoriasis, strongly supporting the notion that these cytokines are involved in the pathobiology of psoriasis disease. In conclusion, findings of the present study suggest that understanding of the functions of these cytokines in the complex pathogenesis of psoriasis disease is of great interest for the future therapeutic intervention.
Keywords: Cytokine; luminex; psoriasis; T helper